التمليح و مرق السمك في الحضارات القديمة من خلال النصوص الادبية والشواهد الاثرية - حماني,صبرينة; زرارقة,محمد نزيم (University of Eloued جامعة الوادي, 2024)
شهد نهاية العصر النيوليتي ظهور الصناعات الحرفية ، و التي تطوّرت وفقا لاحتياجات الإنسان، وذلك راجع لتعدد الوظائف وكذا الظروف الطبيعية والإقليمية والمناخية. وقد اعتبر مجال الصناعات الحرفية من أهمّ المجالات الّتي اهتمّت بها الحضارة القديمة، و يتجلّى ذلك من خلال الشواهد الأدبية، كما تأتي المخلفات المعمارية الّتي لازالت قائمة في المواقع الأثريّة و التي تتمثل في بقايا الورشات كشاهد حي لها ، وقد ضمت هذه الورشات العديد من الصناعات الحرفية، اذ اعتبرت الصناعات الغذائية كتمليح ومرق السمك من ابروها ، كما انها وٌجدت في مختلف المرافق التجاريّة على غرار الأسواق والدكاكين التي بدورها ساهمت في تنمية وازدهار الاقتصاد وانتعاش التجارة الخارجية. Abstract: Arts and crafts appeared during the neolithic period and evolved along with the diversification of human needs and tasks but also according to climate conditions and the ressources available on a regional scale. The archeological remains of workshops gathering multiple production types illustrate quite perfectly its importance. Fish sauce and salting is also one of the most ancient testimonies of human achievments in the field of manufactured products. What allowed that industry to stand the test of time is mainly the quality of its products.. Manufactured goods such as Fish sauce and salting were exposed in various commercial areas besides local markets and were highly praised not only by the roman society but many ancient societies as well. It is that inclination that allowed the city’s economy to reach a certain level of prosperity.
Keywords: قاروم; تمليح; مرق; سمك; ورشات; Garum; Workshops; Fish; Sauce; Salting